A Simple-to-Perform ifn-γ mRNA Gene Expression Assay on Whole Blood Accurately Appraises Varicella Zoster Virus-Specific Cell-Mediated Immunity After Allogeneic Hematopoietic Stem Cell Transplantation - Boccard, Mathilde; Conrad, Anne; Mouton, William; Valour, Florent; Roure-Sobas, Chantal; Frobert, Emilie; Rohmer, Barbara; Alcazer, Vincent; Labussière-Wallet, Hélène; Ghesquières, Hervé; Venet, Fabienne; Brengel-Pesce, Karen; et al. (Frontiers in Immunology, 2022)
Herpes zoster, which is due to the reactivation of Varicella zoster virus (VZV), is a leading cause of morbidity after allogeneic hematopoietic stem cell transplantation (allo-HSCT). While cell-mediated immunity (CMI) is critical to inhibit VZV reactivation, CMI is not routinely assessed due to a lack of reliable tests. In this study, we aimed to evaluate VZV-specific CMI among allo-HSCT recipients (n=60) and healthy individuals (HI, n=17) through a panel of three immune functional assays after ex vivo stimulation by VZV antigen: quantification of (i) IFN-γ release in the supernatants and (ii) T-cell proliferation after a 7-day stimulation of peripheral blood mononuclear cells (PBMC) and (iii) measurement of the ifn-γ mRNA gene expression level after 24 hours of stimulation of a whole blood sample. VZV-responsiveness was defined according to IFN-γ release from VZV-stimulated PBMC. Upon VZV-stimulation, we found that allo-HSCT recipients at a median time of 6 [5-8] months post-transplant had lower IFN-γ release (median [IQR], 0.34 [0.12-8.56] vs 409.5 [143.9-910.2] pg/mL, P < .0001) and fewer proliferating T-cells (0.05 [0.01-0.57] % vs 8.74 [3.12-15.05] %, P < .0001) than HI. A subset of allo-HSCT recipients (VZV-responders, n=15/57, 26%) distinguished themselves from VZV-non-responders (n=42/57, 74%; missing data, n=3) by higher IFN-γ release (80.45 [54.3-312.8] vs 0.22 [0.12-0.42] pg/mL, P < .0001) and T-cell proliferation (2.22 [1.18-7.56] % vs 0.002 [0.001-0.11] %, P < .0001), suggesting recovery of VZV-specific CMI. Interestingly, VZV-responders had a significant fold-increase in ifn-γ gene expression, whereas ifn-γ mRNA was not detected in whole blood of VZV-non-responders (P < .0001). This study is the first to suggest that measurement of ifn-γ gene expression in 24h-stimulated whole blood could be an accurate test of VZV-specific CMI. The routine use of this immune functional assay to guide antiviral prophylaxis at an individual level remains to be evaluated.